Research of the interaction of piles with different lengths and the grillage in the foundations of high-rise buildings = Badania interakcji pali o różnej długości i rusztów w fundamentach budynków wysokich - Pidlutskyi, Vasyl; Boyko, Igor; Nosenko, Viktor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The interaction of piles with different lengths and the grillage in the foundations of high-rise buildings is considered. The numerical modeling of the ?base - foundation - superstructure? system is performed. The redistribution of the efforts in piles depending on the sizes of a foundation slab and the parameters of piles (length and location) is investigated. Typical zones of a foundation such as central, lateral, and angular ones are separated. The redistribution of efforts between piles and a grillage is revealed.
Keywords: pile foundation; pile base; numerical modeling; high-rise buildings; pale fundamentowe; modelowanie numeryczne; budynki wysokie